Posição econômica dos produtores de leite - Leitão e Silva, Josué (Revista Ceres, 2025)
The author analyses the farmer's position in the Be- lo Horizonte milkshed in crder to show how far this position is from the optimum andto indicate how the optimum can be reached easily and economically. He utilizes his M.S. thesis data in the analysis and presents suggestions which farmers can use to reachan ideal position according to economic rationale.